Structural elucidation of chemical compounds from Dysoxylum acutangulum Miq. extract and their antifungal properties against filamentous fungi - Rahman, Mohd Azuar Hamizan (2018)
The search for chemical compounds from plants still needs to be done, because there are still many plants that have not known much about chemical compounds and also the biological activity of the chemical compound that plant. One of native Malaysia’s native plants that has not much been explored much is Dysoxylum acutangulum Miq. was known as Bekak for Malaysian people. The diversity of secondary metabolites from this plant promises a tone of novel finding in various classes of compounds as well as its bioactivities. Fewer studies conducted on antimicrobial activities of Dysoxylum spp., and to the best of our knowledge less studies conducted on its antifungal activities against filamentous fungi. The aim of this study was to elucidate the active compounds from D. acutangulum Miq. bark extract, and also to determine the antifungal properties of each active compounds against filamentous fungi, such as Aspergillus flavus ATTC22546, Aspergillus niger ATTC9029, Beuveria bassiana UPMC28, Cunninghamella echinulata UPMC24, Mucor plembeus UPMC26 and Mucor rouxii UPMC23. Methanol extract of this plant was portioned using chloroform and further fractioned using open column chromatography with different solvent system. The profile of chemical constituent in the fraction was monitored via Thin Layer Chromatography profiling. The isolated compound was further purified using multiple Preparative Thin Layer Chromatography with suitable solvent system. Four compounds successfully isolated and elucidated, they are scopoletin DYC 61 (3.7 mg), 2-hydroxyl-2oxa-cycloarta-23-one-28-oic acid DYC 62 (21.9 mg), 4,29-dihydroxy-31-methyl-3,4-seco-cycloart-23-one-3-oate DYC 81 (92.7mg), and 4-hydroxy-3,4-seco-cycloart-23-one-28-oic acid DYC 42 (3.3 mg). The elucidation of each compound were established using few spectroscopy analysis, such as 1H NMR (500 MHz, CDCl3), 13C NMR (125 MHz, CDCl3), 1H-1H COSY (CDCl3) NMR, HSQC NMR (CDCl3), HMBC NMR (CDCl3), FTIR and HREIMS. The confirmation of the structure was justified by comparing the spectral data with the similar structure of the literature review. Some of the compound didn’t have any FTIR and HREIMS data due to the small amount yield after the isolation process. Four structure compound were being elucidated using the spectroscopy method listed before. One coumarine type compound was isolated and known as Scopoletin, and three of the compounds were belong to cycloartane triterpenoids of secondary metabolites. Two of the cycloartane compound was 3,4- seco-cycloartane (ring A opened) and onther one compound was cycloartane compound with ring A closed. Two compounds, DYC62 and DYC81, were tested for antifungal activity. The results showed that 1% DYC62 reduced 54.55 %, 28.11 %, 64.71 %, 24.35 %, 50.00% and 36.36 % colony size of A. flavus, A. niger, B. bassiana, C. echinulate, M. plembeus, and M. rouxii, rescepectively. Moreover, 1% DYC81 reduced the colony size growth of A. flavus, A. niger, B. bassiana, C. echinulate, M. plembeus, and M. rouxii, with 44.10 %, 18.89 %, 52.94 %, 29.74 %, 30.00 % and 9.09 %, respectively. The conidia growth of A. flavus, A. niger, B. bassiana, C. echinulate, M. plembeus, and M. rouxii can be inhibited with compound DYC 62 with minimum inhibition concentration (MIC) of 2.50 mg/ml, 1.25 mg/ml, 5.00 mg/ml, 2.50 mg/ml, 5.00 mg/ml and 5.00 mg/mL, respectively and can be killed completely with minimum fungicidal activity (MFC) of 2.50 mg/ml, 2.50 mg/ml, 5.00 mg/ml, 2.50 mg/ml, 5.00 mg/ml and 5.00 mg/ml, respectively. Meanwhile MICs and MFCs of compound DYC 81 against conidia of those filamentous fungi ranged between 1.20 mg/ml to >5.00 mg/mL. In conclusion, both compounds, DYC 62 and DYC 81 exhibit antifungal activity against filamentous fungi and have potential to be developed and natural antifungal agents.